Test and Caliberation of Gravity Model For Inter-State Movements of Coal and Foodgrains in India, August 1981 - Planning Commission (Planning Commission, 1981)
This working paper analyzes the application and calibration of the gravity model for forecasting interstate movements of bulk commodities in India, with particular emphasis on coal and foodgrains. Using data from 1978–79, the study compares gravity-based approaches with linear programming models across eight major commodities, evaluating their performance through statistical measures such as R-squared values and the Theil Index. The findings demonstrate that gravity models are especially effective in capturing complex, two-way flows of heterogeneous goods like foodgrains, while linear programming models perform better for homogeneous commodities such as coal. Complementary flow matrix analyses further highlight critical transport corridors, regional resource dependencies, and infrastructure requirements. Overall, the study underscores the importance of adopting appropriate quantitative transport models to support informed policymaking, efficient logistics planning, and balanced regional development in India.
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Government of India Planning Commission (UNDP Transport Policy Planning Project)
Keywords: Gravity Model; Interstate Commodity Flows; Transport Economics; Coal And Foodgrains; Model Calibration Techniques; Linear Programming Model; Bulk Commodity Transportation; Interregional Trade; Transport Policy Planning; Infrastructure Development